Performance enhancement of a dye-sensitized solar cell by peripheral aromatic and heteroaromatic functionalization in di-branched organic sensitizers. (8th May 2018) - Manfredi, N.; Trifiletti, V.; Melchiorre, F.; Giannotta, G.; Biagini, P.; Abbotto, A.
Abstract : Suppression of back reaction and enhanced photoinduced intramolecular electron transfer through peripheral functionalization of triphenylamino based dibranched donor–acceptor dyes. Abstract : Di-branched dyes based on a triphenylamino (TPA) donor core have been functionalized with different aromatic and heteroaromatic peripheral groups bonded to TPA as auxiliary donors and investigated as sensitizers in DSSC. The different aromatic and heteroaromatic substitution significantly perturbed the optical properties of the dyes compared to the unsubstituted TPA reference dye, in turn leading to enhanced photovoltaic performances in terms of photocurrent, photovoltage, and power conversion efficiency (PCE). The enhancement originated from improved strategic interface interactions between the dye-sensitized titania and the liquid electrolyte, as ascertained by current–voltage, quantum efficiency (IPCE), light harvesting properties (LHE), and impedance spectroscopy (EIS) studies.